Chronic peripheral nerve compression disrupts paranodal axoglial junctions. Issue 4 (26th December 2016) - Otani, Yoshinori; Yermakov, Leonid M.; Dupree, Jeffrey L.; Susuki, Keiichiro
ABSTRACT: Introduction: Peripheral nerves are often exposed to mechanical stress leading to compression neuropathies. The pathophysiology underlying nerve dysfunction by chronic compression is largely unknown. Methods: We analyzed molecular organization and fine structures at and near nodes of Ranvier in a compression neuropathy model in which a silastic tube was placed around the mouse sciatic nerve. Results: Immunofluorescence study showed that clusters of cell adhesion complex forming paranodal axoglial junctions were dispersed and overlapped frequently with juxtaparanodal components. These paranodal changes occurred without internodal myelin damage. The distribution and pattern of paranodal disruption suggests that these changes are the direct result of mechanical stress. Electron microscopy confirmed loss of paranodal axoglial junctions. Conclusions: Our data show that chronic nerve compression disrupts paranodal junctions and axonal domains required for proper peripheral nerve function. These results provide important clues toward better understanding of the pathophysiology underlying nerve dysfunction in compression neuropathies. Muscle Nerve 55 : 544–554, 2017